2022
DOI: 10.1093/rheumatology/keac457
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in women with systemic autoimmune rheumatic disorders: a systematic review and meta-analysis

Abstract: Objectives In women with systemic autoimmune rheumatic diseases (SARDs), female sexual dysfunction (SD) remains underestimated. We aimed to explore the prevalence and correlates of SD in females with SARDs. Methods We performed a systematic review and meta-analysis of studies assessing the prevalence of SD and the pooled Female Sexual Function Index (FSFI) scores in this setting (PROSPERO: CRD42021287346). We searched PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 62 publications
0
3
0
1
Order By: Relevance
“…Besonders belastend sind für die PatientInnen dabei die rezidivierenden Konjunktivitiden, welche bei 5 % der PatientInnen als Keratokonjunktivitis sicca auftreten und zu kornealen Ulzerationen (2 %) mit nachfolgenden Einschränkungen des Visus führen können [19]. Zudem sind Karies, Depression, Hyposomnie, sexuelle Dysfunktion, Small-Fiber-Neuropathie und Hyposmie typische und häufige Komorbiditäten [20][21][22]. Entsprechend ist der klinische Phänotyp der SjS vielfältig und individuell sehr unterschiedlich.…”
Section: Klinische Manifestationenunclassified
“…Besonders belastend sind für die PatientInnen dabei die rezidivierenden Konjunktivitiden, welche bei 5 % der PatientInnen als Keratokonjunktivitis sicca auftreten und zu kornealen Ulzerationen (2 %) mit nachfolgenden Einschränkungen des Visus führen können [19]. Zudem sind Karies, Depression, Hyposomnie, sexuelle Dysfunktion, Small-Fiber-Neuropathie und Hyposmie typische und häufige Komorbiditäten [20][21][22]. Entsprechend ist der klinische Phänotyp der SjS vielfältig und individuell sehr unterschiedlich.…”
Section: Klinische Manifestationenunclassified
“…Given a high prevalence of comorbidity between POTS and EDS, there may also be increased rates of these gynecologic complications in POTS patients. Additionally, a systematic review revealed that 63% of women with systemic autoimmune rheumatic diseases, another common comorbidity in POTS, experience sexual dysfunction, which is particularly prevalent in patients with Sjogren's syndrome and systemic sclerosis [17].…”
Section: Sexual Dysfunction and Neurologic Disordersmentioning
confidence: 99%
“…Involvement of the musculoskeletal, pulmonary, cardiovascular, gastrointestinal systems, and, rarely, lower urinary tract in SSc has been demonstrated in many studies [7,8]. In addition, several studies have shown that SSc can cause sexual impairment by causing musculoskeletal pain, joint contractures, vaginal dryness and stenosis, decreased quality of life and physical function, and deterioration in psychological status such as depression [9][10][11][12]. However, research into premature ovarian senescence in these patients is scarce.…”
Section: Systemicmentioning
confidence: 99%